Resveratrol preserves cerebrovascular density and cognitive function in aging mice - Oomen, Charlotte A.; Farkas, Eszter; Roman, Viktor; Van Der Beek, Eline M.; Luiten, Paul G.; Meerlo, Peter (Frontiers in Aging Neuroscience, 2009)
Resveratrol, a natural polyphenol abundant in grapes and red wine, has been reported to exert numerous beneficial health effects. Among others, acute neuroprotective effects of resveratrol have been reported in several models of neurodegeneration, both in vitro and in vivo. In the present study we examined the neuroprotective effects of long term dietary supplementation with resveratrol in mice on behavioral, neurochemical and cerebrovascular level. We report a preserved cognitive function in resveratrol treated aging mice, as shown by an enhanced acquisition of a spatial Y-maze task. This was paralleled by a higher microvascular density and a lower number of microvascular abnormalities in comparison to aging non-treated control animals. We found no effects of resveratrol supplementation on cholinergic cell number or fiber density. The present findings support the hypothesis that resveratrol exerts beneficial effects on the brain by maintaining cerebrovascular health. Via this mechanism resveratrol can contribute to the preservation of cognitive function during aging.